2010
DOI: 10.1002/cjce.20313
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer metrology issues in two‐phase bubble column reactors

Abstract: The metrology and the impact of various parameters and operating conditions on the bulk-to-tube heat transfer coefficients in two-phase bubble columns are investigated on a small-scale mock-up. It is shown that (1) quasi-adiabatic conditions can be reached in the column; (2) the bulk-to-tube heat transfer coefficients for each U-tube downward and upward sections may or may not differ significantly, depending on the way uncertainty of the measurements is estimated; (3) using the different measurements and uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The experimental value of the shell‐side heat transfer coefficient in the column side in similar experimental conditions is around 1122.7 W m −2 K −1 41. The simulated global heat transfer coefficient compares well with this data.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The experimental value of the shell‐side heat transfer coefficient in the column side in similar experimental conditions is around 1122.7 W m −2 K −1 41. The simulated global heat transfer coefficient compares well with this data.…”
Section: Resultssupporting
confidence: 69%
“…The simulated setup is based on an experimental bubble column where temperature and heat transfer data have been measured 41. The column has a diameter of 15.1 cm and is equipped with a bundle of two U‐shaped cooling tubes, each of them being 2.67 cm in diameter.…”
Section: Description Of the Simulated Casesmentioning
confidence: 99%
“…Most academic research on bubble columns has been performed in hollow (empty) ones and the reported studies that involve multiple internals are relatively few . Among these few studies in bubble columns with multiple internals are those of Fair et al, Weinspach and co-workers in the mid-1980‘s and early 1990‘s, Saxena and co-workers in the late 1980‘s and early 1990‘s, Al-Dahhan and co-workers since the mid-2000‘s, and more recently Beliard et al Also, several reviews published by Pandit and Joshi, Saxena and Chen, Saxena, Nigam and Schumpe, Li and Prakash, Kantarci et al, Hulet et al, and more recent Jhawar and Prakash include the details of experimental investigations in empty columns along with some findings in columns with internals. Table summarizes recent reported heat-transfer studies in bubble and slurry bubble columns with multiple internals.…”
Section: Introductionmentioning
confidence: 99%